Ernst Vollrath und Hannah Arendt (Nachruf) - Ludz, Ursula (HannahArendt.net, 2005)
Ernst Vollrath met Hannah Arendt in 1970, through a mutual friend, the Cologne pediatrician Johannes Zilkens. In 1967 he had received his post-doctoral degree (Habilitation) in philosophy from the University of Cologne. On Arendt’s recommendation he got a